2005
DOI: 10.1111/j.1440-1843.2005.00696.x
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic activity in skeletal muscles of patients with non‐hypoxaemic chronic obstructive pulmonary disease studied by 31P‐magnetic resonance spectroscopy

Abstract: Muscle metabolites, during exercise standardized by muscle CSA and MVC, did not differ between non-hypoxaemic COPD patients and control subjects. MVC, CSA or both, are assumed to be closely related to muscle metabolism, as no difference in high energy phosphate metabolites was observed for COPD patients compared to control subjects when the load was standardized for MVC and CSA. This suggests that high energy metabolites are consumed to a similar extent in the same muscle volume in non-hypoxaemic COPD patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Puente-Maestu et al confirmed this phenomenon in COPD muscular biopsies [29], also at the early stage of disease, with an altered mithocondrial electron transport and an increase in ROS, that is a possible cause of systemic oxidative muscular damage. On the other hand, the studies of Ribera [51], Hamaoka [52], Layec [53] and Picard [54] come to a different conclusion: in fact, while confirming the reduced muscular efficiency, they did not show alterations of mitochondrial function and energy production.…”
Section: Discussionmentioning
confidence: 99%
“…Puente-Maestu et al confirmed this phenomenon in COPD muscular biopsies [29], also at the early stage of disease, with an altered mithocondrial electron transport and an increase in ROS, that is a possible cause of systemic oxidative muscular damage. On the other hand, the studies of Ribera [51], Hamaoka [52], Layec [53] and Picard [54] come to a different conclusion: in fact, while confirming the reduced muscular efficiency, they did not show alterations of mitochondrial function and energy production.…”
Section: Discussionmentioning
confidence: 99%
“…Skeletal muscle fibers can change from one fiber type to another, depending on the demand for physical activity. That change in fiber type is observed in the diaphragm of COPD patients, where a fast-to-slow fiber switch phenotype is associated with a significantly reduced diaphragm force [30]. However, a slow-to-fast fiber type shift is a constant finding in lower extremities muscles of patients with COPD, in which fiber-type transitions seem to play an important role [31].…”
Section: Plos Onementioning
confidence: 91%
“…This is important since regional muscle mass has a bad correlation with the overall body muscle mass. Different imaging techniques such as computed tomography, magnetic resonance imaging, positron emission tomography (PET) and ultrasound can also be useful to assess the muscle mass of specific areas in COPD patients (53,(119)(120)(121)(122)(123).…”
Section: Muscle Massmentioning
confidence: 99%